The art of the start : the time-tested, battle-hardened guide for anyone starting anything - Kawasaki, Guy, 1954- (Portfolio, 2004)
Explains how to transform ideas into action, offering a step-by-step approach to launching great products, services, and companies and demonstrating how managers can unleash a creative approach to business at established companies.